Development of azimuth dependent tropospheric mapping functions, based on a high resolution mesoscale numerical weather model, for GNSS data processing - Orliac, Etienne J. (2009)
This thesis is dedicated to the development of two new tropospheric mapping functions for GNSS data processing, based on a high resolution mesoscale numerical weather model (NWM). NWMs have proven to be beneficiary in the processing of GNSS and VLBI data, both for deriving mapping functions and for providing a priori information such as zenith hydrostatic delay (ZHD).